GOOD GOVERNANCE, SECURITY REFORM AND SUSTAINABLE DEVELOPMENT A CASE OF JUBEK STATE - Dr. Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study aimed at investigating the role of Good governance and Security sector reforms on Sustainable development in Jubek State, South Sudan. The objectives of the study were to examine the relationship between Good governance and Sustainable development, assess the relationship between Security reforms and Sustainable development and to study the factor structure of Good governance, Security reforms on Sustainable development. The study employed a case study and descriptive design while using qualitative and quantitative approaches. The study population was 290, selected using purposive and simple random sampling technique. The sample size determination was made using Krejcie and Morgan Table (1970) formula. The sample size was 186 with a response rate of 78.5%. The data analysis was made using Statistical package for social scientists (SPSS 20). The major findings of the study were that there was a positive relationship between; between Good governance and Sustainable development (r = 0.565, P-value < 0.01), relationship between Security reforms and Sustainable development (r = 0.581, P-value < 0.01) and R= 0.691) a combination of Good governance and Security sector reforms in assessing the level to which they can predict the level of Sustainable development in Jubek State. The most influential predictor of Sustainable development being Good governance with (β = .869, Sig. 089) followed by Security sector reforms with (β = .285, Sig. 515) in the model. The study recommends that government of South Sudan should reduce institutional corruption by strengthening them and ensuring policy reforms where necessary. The government should also as a matter necessity promote and ensure transparency, accountability, rule of law and fundamental human rights in the country, the government should restore and develop public goods; restore major infrastructure, including national roads, irrigation systems, and harbors; develop transportation systems to link producers and traders to regional, national, and international markets; and restore security and law enforcement. And that the promotion of good governance by these multilateral institutions should be tailored to the real needs of the people such as reforming the civil service in an effective way that at the same time creates room for employment as opposed to creating unemployment as in the case of the World Bank public service reforms.